2014
DOI: 10.1016/j.amjcard.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Patients With Acute Decompensated Heart Failure Developing After Hospital Admission

Abstract: There are limited data on ADHF that develops after hospital admission. This study sought to compare patient characteristics, comorbidities, mortality, and length of stay by timing of acute decompensated heart failure (ADHF) onset. The surveillance component of the Atherosclerosis Risk in Communities Study (2005–2011) sampled, abstracted, and adjudicated hospitalizations with select ICD-9-CM discharge codes from 4 U.S. communities among those aged 55 years and older. We included 5,602 validated ADHF hospitaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…1,2,4−6 Patel et al demonstrated that short-term mortality in hospital-acquired HF was 3 times the rate of preadmission HF. 4 Patients with hospital-acquired HF had a worse short-term prognosis compared with those with preadmission HF. The authors reported in-hospital mortality of 16%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…1,2,4−6 Patel et al demonstrated that short-term mortality in hospital-acquired HF was 3 times the rate of preadmission HF. 4 Patients with hospital-acquired HF had a worse short-term prognosis compared with those with preadmission HF. The authors reported in-hospital mortality of 16%.…”
Section: Discussionmentioning
confidence: 97%
“…Patel et al reported that 7% of acute HF hospitalizations in patients with the age over 55 had post-admission onset of acute HF or hospitalacquired HF. 4 However, they did not examine the association between uid volume and hospital-acquired HF. Branan et al studied the hidden uid administration, including IV medication, line ushes, blood products, and enteral nutrition, and the development of uid overload, de ned as a positive accumulative uid balance producing weight gain over 10% from baseline, in 219 ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One was that the mean length of stay for patients with acute heart failure is between 5 and 6 days. 12,13 This length of stay contributed to a narrow recruitment and retention window, once patients' conditions were hemodynamically stable. Another factor was the presence of symptoms of acute heart failure and a high number of nonspecific reasons for refusal.…”
Section: Discussionmentioning
confidence: 99%